Sustainability-Oriented HRM, Employee Engagement, and Service Quality in Indonesian Hospitality SMEs: The Mediating Role of Green Organizational Commitment - Siti Farhana Ismail Siti Farhana Ismail; Nguyễn Thị Thu Hà Nguyễn Thị Thu Hà (Oikonomia Review: A Journal of Applied Management, Accounting, and Business Strategy, 2025)
Hospitality SMEs in Southeast Asia face rising expectations to adopt sustainability practices while recovering from demand volatility and workforce turnover. Human resource management plays a central role in translating sustainability goals into everyday service behavior, yet evidence on how sustainability-oriented HRM affects service quality in small hospitality firms remains limited. This study examines how sustainability-oriented HRM practices influence service quality in Malaysian hospitality SMEs through employee engagement and green organizational commitment. Drawing on the Ability–Motivation–Opportunity framework and organizational commitment theory, the model conceptualizes sustainability-oriented HRM as recruitment, training, performance management, and involvement practices aligned with environmental and social responsibility. Survey data were collected from 389 employees across small hotels and restaurants in three Malaysian tourism areas. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test direct effects and parallel mediation. Results indicate that sustainability-oriented HRM strengthens employee engagement and green commitment, which in turn improve perceived service quality. Green commitment partially mediates the HRM–service quality relationship and complements the engagement pathway. The findings suggest that sustainability in hospitality SMEs becomes operationally meaningful when HR practices build psychological attachment to green values and create opportunities for employees to translate those values into customer-facing behavior. Practical implications emphasize aligning training and incentives with sustainability routines, strengthening employee voice, and designing low-cost green engagement practices suitable for SME constraints.